2002
DOI: 10.1159/000067026
|View full text |Cite
|
Sign up to set email alerts
|

The Three-Item Clock-Drawing Test: A Simplified Screening Test for Alzheimer’s Disease

Abstract: The Clock-Drawing Test (CDT) has been used to screen for Alzheimer’s disease (AD) as a supplement to cognitive tests that focus on memory impairment. We examined a comprehensive scoring system of the CDT in screening of AD in a Chinese population and derived a simplified scoring system. All 403 (144 AD and 259 nondemented) subjects were administered the CDT, including both the drawing part (CDT-D) and the copying part (CDT-C). The Cognitive Abilities Screening Instrument and the Clinical Dementia Rating were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 19 publications
2
42
1
Order By: Relevance
“…In general practice, the CDT is in wide use and has been shown to have a sensitivity of about 70-75% and a specifi city of about 65-79% [56] , which is comparable to the present study. However, its practicality is limited especially in subjects with physical handicaps and the results of the present study show that other single-item screening tests give better results.…”
Section: Evaluation Of Single-item Screening Measuressupporting
confidence: 90%
“…In general practice, the CDT is in wide use and has been shown to have a sensitivity of about 70-75% and a specifi city of about 65-79% [56] , which is comparable to the present study. However, its practicality is limited especially in subjects with physical handicaps and the results of the present study show that other single-item screening tests give better results.…”
Section: Evaluation Of Single-item Screening Measuressupporting
confidence: 90%
“…Lin et al [38] derived a simplified system to differentiate early to mild AD in a population in Taiwan. Age and education were significantly related to the CDT, although the correlation was low.…”
Section: Cdt Scoring Systemsmentioning
confidence: 99%
“…The results described above show that both scoring systems had good inter-system and inter-rater reliability and both correlated equally well with the true diagnosis of dementia. Earlier studies by Scanlan et al (2002) and Lin et al (2003) where simple scoring systems were compared to more complex systems, also concluded that the simple systems had a rather good accuracy when compared to the more complex systems.…”
Section: Discussionmentioning
confidence: 97%